Influence Socially Responsible Human Resource Management, Technostress Creators And Employee Satisfaction To Use Fintech (Study On Financial Institutions In Indonesia) - Niki Sanjaya; Ben-Roy Do; Ubud Salim; Wahdiyat Moko (APMBA (Asia Pacific Management and Business Application), 2018)
This study aims to examine and analyze the positive influence between the variables Socially Responsible Human Resource Management (SRHRM), Technostress Creators, employee job satisfaction on the use of Financial Technology (FinTech). The study sample consisted of 152 employees as respondents who worked in several financial institutions in Indonesia, such as banking, securities, insurance and leasing. Data obtained online through Google Form during March to May 2018. Data analysis methods use PLS-SEM to analyze data and verify research hypotheses. The results showed that the results of hypothesis 1) SRHRM had a positive impact on the purpose of using FinTech, 2) SRHRM had a positive impact on Technostress Creators, 3) Technostress Creators had a positive impact on the purpose of using FinTech, 4) SRHRM had a psychological impact on employee job satisfaction when using FinTech, 5) employee job satisfaction has a positive impact on the purpose of using FinTech